Molecular diagnostics of periodontitis - Izabela Korona-Głowniak (Postępy Higieny i Medycyny Doświadczalnej, 2017)
The microorganisms that form dental plaque are the main cause of periodontitis. Their identification and the understanding of the complex relationships and interactions that involve these microorganisms, environmental factors and the host’s health status enable improvement in diagnostics and targeted therapy in patients with periodontitis. To this end, molecular diagnostics techniques (both techniques based on the polymerase chain reaction and those involving nucleic acid analysis via hybridization) come increasingly into use. On the basis of a literature review, the following methods are presented: polymerase chain reaction (PCR), real-time polymerase chain reaction (real-time PCR), 16S rRNA-encoding gene sequencing, checkerboard and reverse-capture checkerboard hybridization, microarrays, denaturing gradient gel electrophoresis (DGGE), temperature gradient gel electrophoresis (TGGE), as well as terminal restriction fragment length polymorphism (TRFLP) and next generation sequencing (NGS). The advantages and drawbacks of each method in the examination of periopathogens are indicated. The techniques listed above allow fast detection of even small quantities of pathogen present in diagnostic material and prove particularly useful to detect microorganisms that are difficult or impossible to grow in a laboratory.